Stimulus-Responsive Nanoporous System Based on a Redox-Active Molecular Self-Assembled Monolayer - Abel, Annik (Langmuir : the ACS journal of surfaces and colloids, 2017)
Ordered arrays of electrically conducting cylindrical nanotubes are created by atomic layer deposition of a thin titanium dioxide layer onto the pore walls of an anodic alumina matrix. All geometric parameters (pore length and diameter and TiO2 layer thickness) are defined and tunable experimentally. The titanium dioxide surface is subsequently functionalized with ferrocenylacetic acid. The chemisorbed ferrocene moieties are oxidized chemically and electrochemically. Monitoring the redox chemistry by UV-visible absorption spectroscopy allows for the quantification of the total density of redox-active units grafted to the surface, as well as the fraction of them oxidized at a given applied potential. The capillary properties of the surface can be adjusted by the applied potential, as quantified by contact angle measurements